The Fish Feed Sector in Kenya, Uganda, Tanzania, and Rwanda: Current Status, Challenges, and Strategies for Improvement—A Comprehensive Review - Jonathan Munguti; Mavindu Muthoka; Mercy Chepkirui; Domitila Kyule; Kevin Obiero; Erick Ogello; Nazael A. Madalla; Gerald Kwikiriza (Aquaculture Nutrition)
This review paper provides an in-depth analysis of the current status, challenges, and strategies for improvement within the fish feed industry in East Africa, focusing on Kenya, Uganda, Tanzania, and Rwanda. Aquaculture production in these countries is experiencing steady growth, driven by increasing demand for fish and fish products for both nutritional and economic purposes. Despite the market facilitating the transition from extensive to semi-intensive and moderately intensive farming systems across the four countries, the sector’s progress is hampered by a lack of sustainable, locally produced, high-quality, and cost-effective fish feeds tailored to different developmental stages of fish. Despite the evident need, there is a notable scarcity of comprehensive reviews addressing the regional perspective of fish feed due to heightened cross-border trade driven by the soaring demand and increased installation of cages in Lake Victoria, as well as in inland dams and reservoirs. This paper addresses critical challenges, such as regional scarcity and limited access to quality feed ingredients, regulatory obstacles, insufficient quality control measures, infrastructure constraints, and a lack of awareness and understanding of feed management and formulation. To overcome these challenges, the paper recommends fostering collaboration to establish a robust regional fish feed supply chain, investing in research and development initiatives, advocating for policy reforms and regulatory support, and compliance with East African Community quality standards for fish feed. Moreover, there is an urgent need to enhance human resource capacity through training and extension services, promote public investment support, strengthen sector institutions and industry associations, conduct training and awareness programs for feed providers, and improve storage facilities to maintain feed quality. The paper provides policymakers with valuable insights to inform targeted interventions that will catalyze positive transformation within the fish feed industry in East Africa.